Revealing the hidden link of the Walker circulation on heavy rainfall patterns in the Eastern Pacific - Byung-Ju Sohn; Jihoon Ryu; Sang-Wook Yeh; Edward Zipser; Chao Liu; Sang-Woo Kim (Communications Earth & Environment)
Abstract Understanding the relationship between tropical heavy rainfall and large-scale circulation provides valuable insights for improving the climate models. Here we use Gaussian Mixture Model to identify two distinct types of heavy rainfall over the tropical Pacific, “strong deep convection” and “moderately strong deep convection,” using satellite-borne precipitation radar measurements. They differ in two typical climatological deep convection-related rainfall modes between the western and eastern Pacific regions. The occurrence frequency of moderately strong deep convection is significantly different between the western and eastern Pacific, potentially linked to the Walker circulation. The enhanced Walker circulation appears to weaken the local Hadley circulation, thereby reducing strong deep convective activity in the eastern Pacific. This increases moderately heavy rainfall and decreases diabatic heating, which can affect global climate. We propose incorporating the close link between large-scale Walker circulation and mesoscale heavy convective rainfall into the current climate models.